Analysis of the Leachate Quality and Its Potential Distribution in the Banjarsari Landfill Environment, Bojonegoro Regency - Nindy Callista Elvania (Jurnal Pendidikan Sains Universitas Muhammadiyah Semarang, 2022)
Leachate treatment is one of the main problems at the Banjarsari landfill because leachate is only accommodated without any processing and can pollute the surrounding environment. This study determined the concentration of leachate quality for several parameters tested (pH, BOD, COD, TSS, Total N, mercury, and cadmium) and compared it with the applicable leachate quality standards, determined the distribution pattern of leachate and determined the effect of the presence of leachate on the surrounding environment. The method used in this study was the grab sample method obtained directly from the monitored leachate body. The test results obtained the average concentration of leachate pH value of 7.55, for the content of organic matter in the leachate for parameters BOD = 91.5 mg/L; COD = 264.5 mg/L and TSS = 83 mg/L, for a total N concentration of 48.5 mg/L, and mercury (Hg) = 0.092 mg/L; and cadmium (Cd) = 0.009 mg/L; The leachate distribution pattern from the Banjarsari landfill followed the ground elevation, that spread in almost all directions where the leachate appeared to lead to irrigation channels and rice fields. Leachate impacted the surrounding environment, such as soil, surface water, and plants.